2012
DOI: 10.1007/s10803-011-1435-2
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic Arousal to Direct Gaze Correlates with Social Impairments Among Children with ASD

Abstract: The present study investigated whether autonomic arousal to direct gaze is related to social impairments among children with autism spectrum disorder (ASD). Arousal was measured through skin conductance responses (SCR) while the participants (15 children with ASD and 16 control children) viewed a live face of another person. Impairments in social skills was assessed with the Developmental, Dimensional and Diagnostic Interview. The level of arousal enhancement to direct gaze in comparison to arousal to faces wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(57 citation statements)
references
References 40 publications
3
47
0
7
Order By: Relevance
“…These findings have been interpreted in terms of reduced motivational salience of social stimuli in this population (Chevallier et al 2012;Dawson et al 1998;Zeeland et al 2010), such that people with ASD have reduced emotional responses to mutual eye contact, so seek out these experiences less than their TD peers. However, Kaartinen et al (2012) also found hypo-arousal in ASD relative to a comparison group in response to averted and closed eyes, suggesting a general hypo-responsiveness to faces rather than to mutual gaze. Joseph et al (2008) found hyperarousal in ASD relative to a comparison group to mutual and averted gaze, and other studies have found no group differences in physiological arousal to mutual gaze between ASD and non-ASD comparison groups (Kylliäinen et al 2012;Kylliäinen and Hietanen 2006;Louwerse et al 2013).…”
Section: Emotional Arousal To Mutual Gazementioning
confidence: 79%
See 2 more Smart Citations
“…These findings have been interpreted in terms of reduced motivational salience of social stimuli in this population (Chevallier et al 2012;Dawson et al 1998;Zeeland et al 2010), such that people with ASD have reduced emotional responses to mutual eye contact, so seek out these experiences less than their TD peers. However, Kaartinen et al (2012) also found hypo-arousal in ASD relative to a comparison group in response to averted and closed eyes, suggesting a general hypo-responsiveness to faces rather than to mutual gaze. Joseph et al (2008) found hyperarousal in ASD relative to a comparison group to mutual and averted gaze, and other studies have found no group differences in physiological arousal to mutual gaze between ASD and non-ASD comparison groups (Kylliäinen et al 2012;Kylliäinen and Hietanen 2006;Louwerse et al 2013).…”
Section: Emotional Arousal To Mutual Gazementioning
confidence: 79%
“…As shown in Table 1, between-group differences show that findings are mixed. Some studies have documented the opposite pattern, finding hypo-arousal to mutual gaze in ASD relative to comparison groups (Kaartinen et al 2012;Stagg et al 2013). These findings have been interpreted in terms of reduced motivational salience of social stimuli in this population (Chevallier et al 2012;Dawson et al 1998;Zeeland et al 2010), such that people with ASD have reduced emotional responses to mutual eye contact, so seek out these experiences less than their TD peers.…”
Section: Emotional Arousal To Mutual Gazementioning
confidence: 99%
See 1 more Smart Citation
“…The authors found increased arousal dudng direct gaze, but only in subjects with ASD. Extending this work, Kaartinen et al (2012) found that autonomie arousal to direct gaze, as measured by skin conductance, was positively correlated with social skills impairments, indicadng that individuals who were more aroused by direct eye contact expedenced greater deficits in social functioning. Combined, these studies suggest that an eye contact deficit may be linked to amygdala activation in some individuals with autism, which, as previously discussed, can be influenced by variations in AVPRla and OXTR, among other genes.…”
Section: Behaviormentioning
confidence: 60%
“…For example, several studies have reported that persons with ASD have difficulties in the processing and labeling of their own emotions, including problems integrating bodily sensations of emotional arousal, recalling previous emotions, and identifying and describing feelings (Capps et al 1992; Hill et al 2004; Losh and Capps 2006; Rieffe et al 2007). Additionally, studies of heart rate variability, pupil size, salivary alpha-amylase, and electrodermal responses have also shown that children with ASD differ from typically developing children in their autonomic responsiveness to viewing human faces as well as when performing other mental tasks (Bal et al 2010; Kaartinen et al 2012; Lioy et al 2011; Martineau et al 2011; Ming et al 2011). …”
Section: Introductionmentioning
confidence: 99%